2022
DOI: 10.1021/acsomega.2c00816
|View full text |Cite
|
Sign up to set email alerts
|

Human Microglia Extracellular Vesicles Derived from Different Microglia Cell Lines: Similarities and Differences

Abstract: Microglial cells are a component of the innate immune system in the brain that support cell-to-cell communication via secreted molecules and extracellular vesicles (EVs). EVs can be divided into two major populations: large (LEVs) and small (SEVs) EVs, carrying different mediators, such as proteins, lipids, and miRNAs. The microglia EVs cargo crucially reflects the status of parental cells and can lead to both beneficial and detrimental effects in many physiopathological states. Herein, a workflow for the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…6 (C to E), in which remarkable variations in both the 1 H and 15 N dimensions were detected for the residues Phe 19 , Ala 21 , Asp 23 , Leu 34 , Gly 37 , Val 39 , and Val 40 , which have been reported to be involved in Aβ fibrillation (41,42). In comparison, small EVs induced only weak changes in the chemical shifts of Phe 19 , Ala 21 , and Gly 37 (fig. S8, C to E).…”
Section: Binding Affinity and Possible Binding Site In Aβ40mentioning
confidence: 92%
See 1 more Smart Citation
“…6 (C to E), in which remarkable variations in both the 1 H and 15 N dimensions were detected for the residues Phe 19 , Ala 21 , Asp 23 , Leu 34 , Gly 37 , Val 39 , and Val 40 , which have been reported to be involved in Aβ fibrillation (41,42). In comparison, small EVs induced only weak changes in the chemical shifts of Phe 19 , Ala 21 , and Gly 37 (fig. S8, C to E).…”
Section: Binding Affinity and Possible Binding Site In Aβ40mentioning
confidence: 92%
“…As shown in Fig. 1A, EVs released by microglia were extracted through gradient centrifugation at 11,000g to isolate the macrosomes and at 100,000g to isolate the small EVs (21). We used Aβ40 peptide as the objective pathological target, as its misfolding and aggregation are widely prevalent in the brains of patients with AD (22) and initiate neurotoxic events including neuroinflammation, synaptic and neuronal loss, and tau-associated pathology (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this idea, researchers started to consider the possibility of exploiting M1polarized microglia as donor cells of exosomes as novel NPs for glioma therapy. [210] Grimaldi et al [211] demonstrated that EVs derived from LPS/ interferon-𝛾 (IFN-𝛾) -treated microglia (referred to as LPS/IFN-𝛾-EVs) injected in the brain of glioma-bearing mice reduced the anti-inflammatory phenotype of TAMs. The reduction of the immunosuppressive phenotypes of TAMs caused a significantly reduced tumor size and tumor-induced neurotoxicity.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Inspired by this idea, researchers started to consider the possibility of exploiting M1‐polarized microglia as donor cells of exosomes as novel NPs for glioma therapy. [ 210 ]…”
Section: Nanostructures Triggering Microglia/macrophage Pro‐inflammat...mentioning
confidence: 99%
“…Proteomic analyses of microglial‐derived exosomes are currently limited by very low protein yield for MS, and lack of definitive verification of their cell of origin. Despite these challenges, several in vitro proteomic studies on microglial‐derived exosomes released in response to inflammatory stimuli have been published [187]. Proteomic analysis of exosomes derived from the N9 microglial cell line identified the composition of microglia‐derived exosomes from cell culture medium [188].…”
Section: Avenues For Proteomics Of Microglia‐derived Exosomesmentioning
confidence: 99%